Frequent Infections, Hypotonia, and Anemia in a Breastfed Infant. Issue 2 (March 2017) - Kamoun, Fatma; Guirat, Rime; Megdich, Fatma; Ben Ameur, Salma; Kallel, Choumous; Hachicha, Mongia
Abstract : Vitamin B12 deficiency may be responsible of serious hematologic and neurodevelopmental abnormalities. We report the case of an infant who was hospitalized because of recurrent infections, failure to thrive, hypotonia, and weakness. He was 8 months old and had been exclusively breastfed. Blood cell count showed pancytopenia with megaloblastic bone marrow. The serum IgG concentration was low. Vitamin B12 level was very low and associated with increased urinary methylmalonic acid. Cobalamin deficiency was caused by mother's unrecognized pernicious anemia. Vitamin B12 supply led to rapid clinical and hematologic improvement.